2018
DOI: 10.1097/pec.0000000000001321
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Poor Prognosis After Severe Head Injury in Children Using Logistic Regression

Abstract: Using these predictors, subsequent exacerbation may be predicted just after arrival at the hospital and appropriate treatment can be provided immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Such findings are compatible with those of Gerlach's study, which followed 39 consecutive children and adolescents and found that EDH was associated with a good outcome [49]. The better outcome was related to the rarity of EDH being associated with intracranial injury and the early diagnosis and initiation of appropriate treatment [50]. Despite its relatively better outcome, EDH is still potentially life-threatening, with a reported mortality rate of up to 4.8% in young children [26].…”
Section: Discussionsupporting
confidence: 87%
“…Such findings are compatible with those of Gerlach's study, which followed 39 consecutive children and adolescents and found that EDH was associated with a good outcome [49]. The better outcome was related to the rarity of EDH being associated with intracranial injury and the early diagnosis and initiation of appropriate treatment [50]. Despite its relatively better outcome, EDH is still potentially life-threatening, with a reported mortality rate of up to 4.8% in young children [26].…”
Section: Discussionsupporting
confidence: 87%
“…In addition to our previous approach to establish the prediction model for severe head injury in Japanese children [25], the present external validation of the TRISS, CRASH, and IMPACT models has clarified their value for use in Japan.…”
Section: Discussionmentioning
confidence: 83%